Pengaruh Teknologi Informasi Terhadap Kinerja Keuangan: Peran Intellectual Capital Sebagai Variabel Moderating - Tarisa Lisandra; Suwandi Suwandi (Journal of Culture Accounting and Auditing, 2023)
This study aims to determine the effect of information technology on financial performance with the role of intellectual capital as a moderating variable. In this study, researchers examined the financial performance of SMA/SMK Muhammadiyah throughout the Gresik Regency by using the independent variables, namely information technology and the moderating variable, namely intellectual capital. The population of this research is SMA/SMK Muhammadiyah in Gresik Regency. Sampling was carried out using a purposive sampling method, and obtained a sample of 40 respondents. The data analysis technique used in this study is SEM-PLS. The results of testing the hypothesis in this study indicate that information technology has a positive and significant effect on financial performance. Meanwhile, intellectual capital is not able to moderate information technology on financial performance. This is because the organization has not been able to develop and manage its intellectual capital properly, where the ability to increase employee motivation is to be able to create new innovations and creativity, and the organization does not yet have a good procedure and structure in improving financial performance so that intellectual capital is said to be lacking good.